In vitro effects of prostaglandin F2? and metamizol on the motility of diluted bull semen - Karahan, Izzet; Turk, Gaffari; Gur, Seyfettin (Tubitak Scientific & Technological Research Council Turkey, 2006)
The purpose of the present study was to investigate in vitro effects of prostaglandin F-2 alpha (PGF(2 alpha)) and metamizol on the motility of diluted bull semen during short-term storage at 4 degrees C. In this study, 3 healthy adult Brown-Swiss bulls, each 3 years old, were used. Semen samples were collected with an artificial vagina. Samples were taken from each bull twice a week over the course of 3 weeks (6 samples per bull). One millilitre of semen was removed from each sample for the determination of semen volume, mass activity, initial motility, sperm concentration, and abnormal sperm rate. The remainder of the semen samples of each bull were diluted to a concentration of 1: 10 (semen: extender) with isotonic sodium citrate + egg yolk solution. The diluted semen samples were then divided into 12 sterile tubes of equal volume (0.5 ml). Different amounts of PGF(2 alpha) [0 (PGF(2 alpha)-free), 125, 250, 500, 1000, and 1500 mu g] were added to 6 of these samples at 37 degrees C. Similarly, different amounts of metamizol [0 (metamizol-free), 125, 250, 500, 1000, and 1500 mu g] were added to the other 6 samples at 37 degrees C. After the supplementation of PGF(2 alpha) or metamizol, all semen samples were stored at 4 C. The sperm motility of the samples was examined at 0, 1, 2, 4, 24, 48, 72, 96, 120, 144, 168, 192, and 216 h. No significant differences in spermatological characteristics were determined between the bulls. Sperm supplementation with 125 mu g and 250 mu g PGF(2 alpha) caused a statistically significant increase (P < 0.05) in the motility of diluted semen stored at 4 C after 24 h versus diluted PGF(2 alpha)-free semen. However, the supplementation with 500 mu g and 1000 mu g PGF(2 alpha) caused significant motility decreases after 4 h, while 1500 mu g PGF(2 alpha) also caused a decrease after 2 h compared to diluted PGF(2 alpha)-free semen (P < 0.05). On the other hand, metamizol supplementation of 125 mu g and 250 mu g significantly decreased the motility of diluted semen stored at 4 degrees C after 48 hand 24 h, respectively, while 500 mu g, 1000 mu g, and 1500 mu g of metamizol reduced motility after 4 h ( P < 0.05) in comparison to the diluted metamizol-free semen.
Keywords: bull; semen; PGF(2 alpha); metamizol; sperm motility